2003
DOI: 10.1046/j.0931-2048.2003.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ivermectin and doramectin faecal residues on the invertebrate colonization of cattle dung

Abstract: The effects of avermectin [ivermectin (IVM) and doramectin (DRM)] faecal residues on dung colonization and degradation by invertebrates were evaluated during late spring in the east of La Pampa province, Argentina. The study was conducted after collection of faecal material from animals (10 steers per group) allocated to the following groups: untreated control group (CG) and groups treated subcutaneously (200 μg/kg) with either DRM (DG) or a long‐acting formulation of IVM (IG). Fifty pats (550 g each) per grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 35 publications
6
51
1
4
Order By: Relevance
“…In agreement with Sommer et al (1992) and Suárez et al (2003), the highest concentrations of ivermectin were detected 3 days after treatment. Meanwhile, the concentrations in faecal samples collected 1 and 3 days after treatment were significantly higher than in those collected later, regardless of the period of environmental exposure.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In agreement with Sommer et al (1992) and Suárez et al (2003), the highest concentrations of ivermectin were detected 3 days after treatment. Meanwhile, the concentrations in faecal samples collected 1 and 3 days after treatment were significantly higher than in those collected later, regardless of the period of environmental exposure.…”
Section: Discussionsupporting
confidence: 69%
“…In addition, the drug concentrations at 7 dpt were also higher than those collected afterwards. Ivermectin concentrations in the present study were higher than those detected in La Pampa province for similar after-treatment and afterdeposition times (Suárez et al 2003). These differences could be explained by the different experimental models used in both investigations, as well as by the different seasonal conditions in both regions.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…These results indicate slow degradation of Iv in dung and agree with previous field studies. Suarez et al (2003) suggested DT 50 s of up to 180 days in cattle dung (180 days after deposition of the dung pats, 10-57% of the initially applied Iv concentration was detected), and Sommer et al (1992) observed no biodegradation within 45 days. Table 3 shows the measured concentrations in soil at the end of the experiment.…”
Section: Ivermectin Concentrations In Dung Runoff and Drainage Watermentioning
confidence: 95%